2021
DOI: 10.1136/bmjgast-2020-000578
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal mucosal damage in patients with COVID-19 undergoing endoscopy: an international multicentre study

Abstract: BackgroundAlthough evidence suggests frequent gastrointestinal (GI) involvement during coronavirus disease 2019 (COVID-19), endoscopic findings are scarcely reported.AimsWe aimed at registering endoscopic abnormalities and potentially associated risk factors among patients with COVID-19.MethodsAll consecutive patients with COVID-19 undergoing endoscopy in 16 institutions from high-prevalence regions were enrolled. Mann-Whitney U, χ2 or Fisher’s exact test were used to compare patients with major abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 37 publications
2
67
0
11
Order By: Relevance
“…Understanding the pathogenesis and the mechanisms for transmission is of utmost importance. A growing body of literature suggests that replication at the level of the gastrointestinal (GI) tract not only occurs in a large proportion of cases 2,3 , but it also extends the overall duration of shedding, after viral clearance from the respiratory tract has occurred 4 . Moreover, SARS-CoV-2 has been detected in adult stool samples 5 and in air samples of patients' toilet areas 6 .…”
mentioning
confidence: 99%
“…Understanding the pathogenesis and the mechanisms for transmission is of utmost importance. A growing body of literature suggests that replication at the level of the gastrointestinal (GI) tract not only occurs in a large proportion of cases 2,3 , but it also extends the overall duration of shedding, after viral clearance from the respiratory tract has occurred 4 . Moreover, SARS-CoV-2 has been detected in adult stool samples 5 and in air samples of patients' toilet areas 6 .…”
mentioning
confidence: 99%
“…Recent reports have indicated the damage in the gastrointestinal mucosal barrier in COVID-19 patients (Massironi et al, 2020;Sharma and Riva, 2020;Vanella et al, 2021). The damage in the mucosal barrier may cause the digestive enzymes of the exocrine pancreas to enter into the systemic circulation (Altshuler et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter international study of 114 endoscopies performed on COVID-19 patients for acute GI bleeds, found that 25% of bleeds were caused by ulcers, 16% by erosive/ulcerative gastro-duodenopathy and 9% by petechial or hemorrhagic gastropathy (85). Utilizing multivariate regression analysis, the authors found that ICU admission, pre-existing frailty, and extended hospitalization had no impact on the risk of a positive endoscopy finding (85).…”
Section: Gi Bleedingmentioning
confidence: 99%